The medial prefrontal cortex is crucial for the maintenance of persistent licking and the expression of incentive contrast - Parent, Marc A.; Amarante, Linda M.; Liu, Benjamine; Weikum, Damian; Laubach, Mark (Frontiers in Integrative Neuroscience, 2015)
We examined the role of the medial prefrontal cortex (mPFC) in reward processing and the control of consummatory behavior. Rats were trained in an operant licking procedure in which they received alternating access to solutions with relatively high and low levels of sucrose (20% and 4%, w/v). Each level of sucrose was available for fixed intervals of 30 seconds over 30 minute test sessions. Over several days of training, rats came to lick persistently when the high level of sucrose was available and suppressed licking when the low level of sucrose was available. Pharmacological inactivations of the mPFC, specifically the rostral part of the prelimbic area, greatly reduced intake of the higher value fluid and only slightly increased intake of the lower value fluid. In addition, the inactivations altered within-session patterns and microstructural measures of licking. Rats licked equally for the high and low levels of sucrose at the beginning of the test sessions and “relearned” to reduce intake of the low value fluid over the test sessions. Durations of licking bouts (clusters of licks with inter-lick intervals <0.5 sec) were reduced for the high value fluid and there were many more brief licking bouts (<1 sec) when the low value fluid was available. These effects were verified using an alternative approach (optogenetic silencing using archaerhodopsin) and were distinct from inactivation of the ventral striatum, which simply increased overall intake. Our findings suggest that the mPFC is crucial for the maintenance of persistent licking and the expression of learned feeding strategies.